Сучасні освітні технології - Почуєва, В. В.; Pochuyeva, V. V.; ORCID https://orcid.org/0000-0003-1021-3627 (The world of science and innovation: Abstracts of the 2nd International scientific and practical conference (London, United Kingdom, 2020). - Cognum Publishing House. ‒ P. 470-475, 2020)
У статті розглянуто деякі сучасні освітні технології як ефективні засоби організації продуктивного педагогічного середовища, що сприяють підвищенню мотивації, пізнавальної активності та якості підготовки майбутніх фахівців у вищих навчальних закладах.

The article considers some modern educational technologies as effective means of organizing a productive pedagogical environment that help to develop motivation, cognitive activity and quality of training of future professionals in higher educational establishments.

В статье рассмотрены некоторые современные образовательные технологии как эффективные средства организации продуктивной педагогического среды, способствующие повышению мотивации, познавательной активности и качества подготовки будущих специалистов в высших учебных заведениях.
Почуєва, В. В. Сучасні освітні технології / В. В. Почуєва // The world of science and innovation: Abstracts of the 2nd International scientific and practical conference (London, United Kingdom, 2020). - Cognum Publishing House. ‒ P. 470-475.
Keywords: діяльнісний підхід; саморозвиток; співробітництво; тандемне навчання; activity approach; self-development; cooperation; tandem training; деятельностный подход; саморазвитие; сотрудничество; тандемное обучение; Наукові публікації. Scientific publications. Научные публикации; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика